Prevalence of hypertension and associated factors in a rural community in Bayelsa State - Egbi, Oghenekaro G.; Ogoina, Dimie; Oyeyemi, Abisoye (International Journal of Research in Medical Sciences, 2018)
Background: Hypertension is considered among the most common non-communicable diseases globally with significant morbidity and mortality. Closely related to it is pre-hypertension, a category between hypertension and normotension which is believed to be a forerunner to hypertension and cardiovascular disease. Hypertension has been on the increase in recent times, even in rural communities which were previously less affected. The study was carried during the world health day as a screening exercise to determine the prevalence of hypertension and its associated factors in a rural community. Methods: This cross-sectional study was conducted in Ogboloma village, a small rural community in Bayelsa State, Ngeria Consecutive sampling of all eligible participants who presented for the screening exercise was done. Socio-demographic data, clinical history, anthropometry and blood pressure were taken. Data was stored and analyzed using SPSS version 20.0. Results: One hundred and thirty-one participants completed the study. There were 49(37.4%) males. The prevalence of hypertension was 50.4% while pre-hypertension was found in another 41.2%. Factors associated with hypertension on univariate analysis were age (p <0.001) body mass index (p=0.038) waist hip ratio (p=0.008) hyperglycemia (p=0.030) and smoking (p=0.009) However, only age (p=0.004) and smoking (p=0.037) remained significant on multivariate analysis. Conclusions: Hypertension and Pre-hypertension were highly prevalent in this rural community. Age and smoking were significant predictors of hypertension. Hypertension screening and control programmes should therefore target rural communities and smokers.